2022
DOI: 10.1111/jog.15158
|View full text |Cite
|
Sign up to set email alerts
|

Expression of extracellular matrix proteins nidogen‐1 and legumain in endometrial carcinomas

Abstract: Purpose: Our purpose was to comparatively investigate the expressions of nidogen-1 (NID1) and legumain (LGMN) in patients with endometrial cancer, endometrial intraepithelial neoplasia, and proliferative endometrium. Methods: A cross-sectional, single-center study was performed by the obstetrics and gynecology and pathology departments of our institution. The relationships between descriptive data, clinicopathologic information, and immunohistochemical expressions of NID1 and LGMN were investigated. Results: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…A previous study reported that the L1CAM [386], HSD17B2 [387], GRP (gastrin releasing peptide) [388], FABP4 [389], SOX6 [390]. MMP12 [391], APOD (apolipoprotein D) [392], LAG3 [393], CST1 [394], FLT1 [395], DHCR24 [396], PRL (prolactin) [397], WNT5A [398], TIMP3 [399], CD24 [400], LHCGR (luteinizing hormone/choriogonadotropin receptor) [401], MMRN1 [402], CD4 [403], ADAMTS5 [404], ADAMTS1 [405], PADI2 [406], MARK1 [407], KL (klotho) [408], PLAU (plasminogen activator, urokinase) [409], SOX8 [410], CRABP2 [411], PTPRD (protein tyrosine phosphatase receptor type D) [412], EPCAM (epithelial cell adhesion molecule) [413], IRX2 [414], SEMA3B [415], CYP1A1 [416], PDGFD (platelet derived growth factor D) [417], LEPR (leptin receptor) [418], APOE (apolipoprotein E) [419], CASP1 [420], MGLL (monoglyceride lipase) [421], NID1 [422], ABCG2 [423], ACE (angiotensin I converting enzyme) [424], PGR (progesterone receptor) [425], HPSE2 [426], LMTK3 [427], ALPP (alkaline phosphatase, placental) [428], EGFL6 [429], CACNA2D3 [430], MCTP1 [431], HKDC1 [432], S100A4 [433], MACC1 [434], MMP3 [435], FGFR2 [436], IL33 [437], FOXC2 [438], ITGA7 [439], EFEMP1 [440], GATA6 [441], BHLHE41 [442], TCF21 [443], GDF10 [444], NKX3-1 [445], AKR1C3 [446], SGK1 [447], RAP1GAP [448], FLI1 [449], NOX4 [450], SERPINE2 [451], IGSF9 [452], IGF2BP1 [453], SALL4 [454], VDR (vitamin D receptor) [455], CELSR2 [456],...…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that the L1CAM [386], HSD17B2 [387], GRP (gastrin releasing peptide) [388], FABP4 [389], SOX6 [390]. MMP12 [391], APOD (apolipoprotein D) [392], LAG3 [393], CST1 [394], FLT1 [395], DHCR24 [396], PRL (prolactin) [397], WNT5A [398], TIMP3 [399], CD24 [400], LHCGR (luteinizing hormone/choriogonadotropin receptor) [401], MMRN1 [402], CD4 [403], ADAMTS5 [404], ADAMTS1 [405], PADI2 [406], MARK1 [407], KL (klotho) [408], PLAU (plasminogen activator, urokinase) [409], SOX8 [410], CRABP2 [411], PTPRD (protein tyrosine phosphatase receptor type D) [412], EPCAM (epithelial cell adhesion molecule) [413], IRX2 [414], SEMA3B [415], CYP1A1 [416], PDGFD (platelet derived growth factor D) [417], LEPR (leptin receptor) [418], APOE (apolipoprotein E) [419], CASP1 [420], MGLL (monoglyceride lipase) [421], NID1 [422], ABCG2 [423], ACE (angiotensin I converting enzyme) [424], PGR (progesterone receptor) [425], HPSE2 [426], LMTK3 [427], ALPP (alkaline phosphatase, placental) [428], EGFL6 [429], CACNA2D3 [430], MCTP1 [431], HKDC1 [432], S100A4 [433], MACC1 [434], MMP3 [435], FGFR2 [436], IL33 [437], FOXC2 [438], ITGA7 [439], EFEMP1 [440], GATA6 [441], BHLHE41 [442], TCF21 [443], GDF10 [444], NKX3-1 [445], AKR1C3 [446], SGK1 [447], RAP1GAP [448], FLI1 [449], NOX4 [450], SERPINE2 [451], IGSF9 [452], IGF2BP1 [453], SALL4 [454], VDR (vitamin D receptor) [455], CELSR2 [456],...…”
Section: Discussionmentioning
confidence: 99%
“…In their very recent study, the authors investigated correlation of endometrial carcinoma to Legumain expression in human endometrium. Patients with higher Legumain expression were more likely to have higher carcinoma grade as well as carcinoma recurrence ( 38 ). Therefore, one could expect, that reducing the endometrial activity by losing weight and normalizing hormonal balance should result in down-regulation of Legumain expression in the endometrium, but our findings suggest just the opposite effect.…”
Section: Discussionmentioning
confidence: 99%